Reactive Oxygen Species Interact With NLRP3 Inflammasomes and Are Involved in the Inflammation of Sepsis: From Mechanism to Treatment of Progression - Zhao, Shuai; Chen, Fan; Yin, Qiliang; Wang, Dunwei; Han, Wei; Zhang, Yuan (Frontiers in Physiology, 2020)
Over the past 10 years, the crisis of sepsis has remained a great challenge. According to data from 2016, the sepsis-related mortality rate remains high. In addition, sepsis consumes extensive medical resources in intensive care units, and anti-inflammatory agents fail to improve sepsis-associated hyperinflammation and symptoms of immunosuppression. The specific immune mechanism of sepsis remains to be elucidated. Reactive oxygen species (ROS) are triggered by energy metabolism and respiratory dysfunction in sepsis, which not only cause oxidative damage to tissues and organelles, but also directly and indirectly promote NOD-, LRR-, and pyrin domain-containing protein 3 (NLRP3) inflammasome activation. NLRP3 inflammasomes enlarge the inflammatory response and trigger apoptosis of immune cells to exacerbate sepsis progression. Inhibiting the negative effects of ROS and NLRP3 inflammasomes therefore provides the possibility of reversing the excessive inflammation during sepsis. In this review, we describe the interaction of ROS and NLRP3 inflammasomes during sepsis, provide prevention strategies, and identify fields that need further study.